2016
DOI: 10.1073/pnas.1516139113
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic skeletal muscle-powered adaptive biological machines

Abstract: Complex biological systems sense, process, and respond to their surroundings in real time. The ability of such systems to adapt their behavioral response to suit a range of dynamic environmental signals motivates the use of biological materials for other engineering applications. As a step toward forward engineering biological machines (bio-bots) capable of nonnatural functional behaviors, we created a modular light-controlled skeletal musclepowered bioactuator that can generate up to 300 μN (0.56 kPa) of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
277
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 252 publications
(301 citation statements)
references
References 26 publications
(34 reference statements)
6
277
0
Order By: Relevance
“…2c). These bio-hybrid systems can incorporate muscle tissue, such as those engineered from the C2C12 line of mouse myoblasts, directly into soft systems 17,45 . For these systems, actuation can be induced by applying electrical or optical impulses.…”
Section: Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…2c). These bio-hybrid systems can incorporate muscle tissue, such as those engineered from the C2C12 line of mouse myoblasts, directly into soft systems 17,45 . For these systems, actuation can be induced by applying electrical or optical impulses.…”
Section: Combustionmentioning
confidence: 99%
“…For these systems, actuation can be induced by applying electrical or optical impulses. These actuators show directional locomotion and can benefit from 'exercise' training, thus highlighting the ability of bio-hybrid machines to adapt to their environment 45 .…”
Section: Combustionmentioning
confidence: 99%
“…[120] Taking advantage of the precise spatiotemporal control over muscle contraction enabled by optogenetics, we showed that directional locomotion and 2D rotational steering could be accomplished in completely symmetric structures (Figure 10A). Additionally, we showed that an "exercise" regimen of daily optical stimulation significantly enhanced muscle force production, and coupling optical and mechanical stimulation led to a further synergistic increase in muscle performance.…”
Section: Use Of Engineered Tissue As Biohybrid Machine Componentsmentioning
confidence: 99%
“…The modularity of these subunits (consisting of cells, tissues, and biomaterials, along with growth factors or other biochemical signals) allows for "forward-engineering" of the system by assembling the components in a diverse manner, like building blocks, thus expanding the functionality of the system. For example, we recently demonstrated a modular skeletal muscle tissue "ring" that could be coupled to a three-dimensional (3D)-printed skeleton to produce net motion 2 . This bio-integrated actuator (bio-bot) was a functional cellular system that exhibited dynamic and adaptive behavior based on both its inherent design and its surroundings.…”
Section: Introductionmentioning
confidence: 99%